KEMAMPUAN PETUGAS DALAM PENERBITAN SURAT IZIN USAHA MIKRO KECIL di KANTOR CAMAT DUNGINGI KOTA GORONTALO - Ellys Rachman; Lisda Van Gobel; Andi Yusuf Katili; Tety Adam (Jurnal Administrasi, Manajemen dan Ilmu Sosial, 2023)
This study aims to see the ability of officers in issuing small business licenses (UMK) at the Dungingi sub-district office in Gorontalo City. The focus of this research are the level of accuracy, responsibility, and work initiative. This research uses descriptive qualitative research. Data interview techniques used observation techniques, interviews, and secondary data recording. Under the type of research used, the data analysis technique used is qualitative analysis techniques.The results showed that: research on the ability of officers in issuing micro and small business licenses at the place. The city which is seen from the aspect of the level of accuracy, responsibility, and work initiative is still lacking and has not supported the Micro and Small Business.The suggestion in this research is the need for the problems identified in this study, such as a lack of accuracy, less responsibility, and less work initiative from employees, which can be used as benchmarks or recommendations for improving work quality.